University students’ strategies of coping with stress during the coronavirus pandemic: Data from Poland - Babicka-Wirkus, Anna; Wirkus, Lukasz; Stasiak, Krzysztof; Kozłowski, Paweł (PLOS ONE, 2021)
The COVID-19 pandemic has changed the functioning of universities worldwide. In Poland, the transfer to online teaching was announced without prior warning, which radically changed students’ daily functioning. This situation clearly showed the students’ helplessness and difficulties with coping with this new, stressful situation, highlighted in many previous studies. A sudden and far-reaching change in daily functioning caused anxiety, depression, and stress in this group. Thus, from a pedagogical and psychological point of view, it is pertinent to examine the students’ strategies of coping with stress caused by the COVID-19 pandemic. To this end, in 2020, a sample of Polish students was anonymously measured using the Mini-COPE questionnaire. Data was gathered from 577 students from 17 universities. The statistical analysis showed that during the coronavirus pandemic, Polish students most often used the coping strategies of: acceptance, planning, and seeking emotional support. Such factors as age, gender, and place of residence influenced the choice of specific strategies of coping with stress during the COVID-19 pandemic. The results also showed that the youngest students had the lowest coping skills. The results allow for concluding that the students’ maladaptive strategies of coping with stress, especially during the pandemic, may result in long-term consequences for their psychophysiological health and academic achievements. Thus, based on the current results and on the participatory model of intervention, a support program for students is proposed which would involve psychological, organizational, and instrumental support.